Kompetencetilegnelse af klinisk lederskab i sygepleje - Camilla Bernild; Louise Støier; Vibeke Røn Noer; Mari Holen (Tidsskrift for Professionsstudier)
Clinical leadership is a central and dominant educational concept in nursing education expressed in learning objectives. However, we know very little about how clinical leadership takes shape in clinical practice and how it is acquired, which we explore in this article. The article is based on institutional ethnography combined with educational theory on competence acquisition, consisting of three domains: qualification, socialization, and subjectification. The empirical material is produced through ethnographic fieldwork as part of an educational experiment where a new examination of clinical leadership is being tested. The analysis shows that competence acquisition in clinical leadership is characterized by contradictions between the domains of qualification, socialization, and subjectification. On the one hand, clinical leadership is a dominant educational concept that, through the qualification of students, has the potential to contribute to desirable changes in practice, which the new educational approach seems to support. On the other hand, clinical leadership is an empty concept that attaches itself to very different clinical practices with historically anchored norms that strongly influence socialization into clinical leadership. In some cases, clinical leadership becomes a matter of subordinating and adapting care to collaborators. Consequently, subjectification to clinical leadership provides relatively little room for freedom of action and exercise of authority - regardless of the intentions of the education.